Genome-Scale CRISPR-Cas9 Transcriptional Activation Screening in Metformin Resistance Related Gene of Prostate Cancer - Chen, Jiahong; Huang, Yaqiang; Tang, Zhenfeng; Li, Maozhang; Ling, Xiaohui; Liao, Jinxian; Zhou, Xiaobo; Fang, Shumin; Zhao, Haibo; Zhong, Weide; Yuan, Xia (Frontiers in Cell and Developmental Biology, 2021)
Metformin is a classic type II diabetes drug which possesses anti-tumor properties for various cancers. However, different cancers do not respond to metformin with the same effectiveness or acquire resistance. Thus, searching for vulnerabilities of metformin-resistant prostate cancer is a promising strategy to improve the therapeutic efficiency. A genome-scale CRISPR-Cas9 activation library targeting 23430 genes is conducted to identify the genes that confer resistance to metformin in prostate cancer cells. Candidate genes were selected by total reads of sgRNA and sgRNA diversity, and then CCK8 assay was used to verify their resistance to metformin. Interestingly, we discovered that the activation of ECE1, ABCA12, BPY2, EEF1A1, RAD9A, NIPSNAP1 contributed to in vitro resistance to metformin in DU145 and PC3 cell lines. Notably, high level of RAD9A, with poor prognosis in PCa, is the most significant gene in CCK8 assay. Furthermore, we discerned the tumor immune microenvironment with RAD9A expression by CIBERSORT. These results suggested that high level of RAD9A may up-regulate regulatory T cells to counterbalance metformin in tumor immune microenvironment.